BOOK REVIEW: IN THIS WORLD OF WONDERS. MEMOIR OF A LIFE IN LEARNING - M. Laubscher (Acta Theologica, 2020)
Wolterstorff, N. (Grand Rapids, MI: Wm B. Eerdmans, 2019), 334pp. Price: R447. ISBN: 978-0-8028-7679-9 is reviewed by M. Laubscher.